Clinical Outcome and Quality of Life in Patients of Lefort Fractures - Rashid, Tania; Nazir Chaudhary, Asif; Sauban Raza, Muhammad; Aslam, Zeeshan (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: Maxillofacial fractures are a growing concern globally due to their increasing incidence, associated injuries, morbidity, disfigurement, function loss, economic implications, and postoperative quality of life issues. The objective of the study is to determine the clinical outcome and quality of life in patients with Lefort fractures. Methodology: The present research is an observational and descriptive investigation, including a sample of 53 patients diagnosed with Lefort fracture. The study was done at the Nishtar Institute of Dentistry in Multan, Pakistan, spanning from September 2023 to February 2024. Following the endorsement of the research by the Ethical Review Board of the hospital, patients were recruited using a nonprobability sequential sampling method. The researchers used a self-constructed questionnaire as a means of evaluating clinical outcomes and quality of life that occurred after a Lefort fracture. The data underwent statistical analysis, and findings and observations were derived from the analysis. Results: The study examined the outcomes of different treatments for patients with Le Fort fractures, focusing on Type I, Type II, and Type III fractures. open reduction is performed on 12 patients with Type I, 12 patients with Type II, and 7 patients with Type III Lefort fractures. On the other hand, conservative therapy is performed on 3 patients with Type I, 9 patients with Type II, and 10 patients with Type III Lefort fractures. Results showed that open reduction led to more consistent improvements across various symptoms and complications compared to conservative therapy. Patients experienced pain in the mouth/face area, chewing difficulties, aesthetic deformity, daily routine activity improvement, neurosensory deficit improvement, malocclusion correction, and mastication improvement. Practical Implication: The study reveals that open reduction is a more effective treatment for Le Fort fractures than conservative therapy, especially in patients with significant pain, chewing difficulties, aesthetic deformities, or malocclusion, resulting in better functional and aesthetic outcomes and improved quality of life. Conclusions: Le Fort fractures are three types of injuries to the midface region, each resulting from different impacts in traffic accidents. Type I fractures occur from direct impact to the front of the face, involving a horizontal separation of the maxilla from the craniofacial skeleton. Type II fractures involve a pyramidal separation of the midface, resulting from vertical force transmission from head-on collisions or severe frontal impacts. Specific facial bone fracture patterns result from blunt face trauma. Though uncommon, they are commonly linked to other serious head and neck injuries and have low fatality rates. Before therapy, Le Fort fracture patients had a much worse psychological quality of life. Refer patients to psychologists or psychiatrists for further assessment and treatment of remaining psychological and social relationship difficulties.